LONELY-GUY Knocks Every Door: Crosskingdom Microbial Pathogenesis. (December 2015) - Naseem, Muhammad; Sarukhanyan, Edita; Dandekar, Thomas
Abstract : Many plant microbial pathogens utilize cytokinins to establish interactions with their host. However, the production of cytokinins by an animal pathogen has just been reported for the first time. Here we discuss the impact of microbial secreted cytokinins on the infection dynamics in plant and animal cells.